The current research aimed to investigate the level of self-affirmation among battered married female students (Journal of the College of Basic Education, 2024)
And the significance of the differences in the relative relationship between the affirmation of the relationship between abused married students according to specialization (scientific and humanitarian), with its research objectives, where the researcher measured the self-affirmation, and after completing the procedures for constructing validity and reliability, the scale consisted of (40) items. The researcher measured the scale on The establishment of (400) abused married female students from the College of Basic Education / Al-Mustansiriya University was able to For statistical analysis (SPSS descriptive applications and software)The researcher reached the following results: a low level of self-affirmation among students who are married to abused women, and there are no differences in the relationship between self-affirmation according to scientific and humanities specializations